Determinants of capital structure: empirical evidence from listed banks of Malaysia - Tam, Jhet Tsing (2022)
The purpose of this study is to explore the dynamics behind the drivers of the capital structure of Malaysia's publicly traded banks. In Malaysia's developing economy, listed banks play a significant role as financial catalysts, leading to the investigation of 10 listed banks for the period 2014 to 2020. This study aims to examine the influence and relationship of 6 bank-specific factors: probability, size, growth rate, asset tangibility, risk, and tax, as well as two macroeconomic factors: inflation and GDP growth on bank leverage which is chosen as the dependent variable. THe explanatory variables are tested using multiple linear panel regressions model, i.e. Ordinary least squares (OLS), fixed effects (FE) and random effects (RE). THe regression results from this study have provided mixed results supporting both the trade-off and pecking order theory. Leverage is found to have a negative correlation with profitability, growth, tax and GDP growth whereas a positive relation is found against size, asset tangibility, risk and inflation. From the results, only 50% of independent variables exhibit the predicted correlations, and that 4 variables are found to have a significant impact on the determinants of bank capital structure in Malaysia.